Sharpe's peril [videorecording (DVD)] - Clegg, Tom; Bean, Sean; O'Malley, Daragh; Cochrane, Michael; Cornwell, Bernard (Distributed by Warner Home Video, 2013)
Lieutenant Colonel Richard Sharpe and Sergeant Major Patrick Harper are traveling across India, escorting the beautiful Marie-Angelique Bonnet to meet her fiancé. While in bandit-plagued badlands, they come across the very dregs of the Crown's troops: an ill disciplined, rag-tag unit led by boy soldier Beauclare. As Sharpe and company sit down to have dinner with their hosts, the camp comes under attack by bandit Chitu. When the dust settles, it becomes apparent there have been many casualties and Sharpe realizes that he is the only person now capable of getting this wagon train to the safety of the next army garrison.